Choosing a Drinking Water Source Pattern in India: A Study of Households - Subhalakhsmi Paul (Recent Trends in Arts and Social Studies Vol. 6, 2023)
In India, freshwater availability is projected to be 1545 m3/year per person, which is below the threshold of minimal demand and makes drinking water a precious resource. In the next ten years, water stress is anticipated to reach epic proportions because India is home to around 16 percent of the world’s population but just 4 percent of its water resources. More information about the preferred water source for families is needed in order to increase the success of water delivery programmes. Using nationally representative data on urban households from the Indian Human Development Survey from 2005, we attempt to predict the choice of drinking water source in urban India in this research. Our findings indicate that financial capability and benefit awareness.